Precipitation of hydroxyapatite at 37 °C in a meso oscillatory flow reactor operated in batch at constant power density. Issue 12 (29th July 2013) - Castro, Filipa; Ferreira, António; Rocha, Fernando; Vicente, António; Teixeira, José António
<x xml:space="preserve">Abstract</x> A meso oscillatory flow reactor (meso‐OFR) was successfully applied for the precipitation of hydroxyapatite (HAp) nanoparticles. Mixing efficiency of the mesoreactor operated batchwise in a vertical tube was evaluated at constant power density, by monitoring variation of hue values upon mixing both spatially and temporally. The best operating conditions for fast mixing and a more homogeneous reaction medium were verified for f = 0.83 Hz and x0 = 4.5 mm. HAp precipitation was then carried out under these conditions at 37 °C for different mixing Ca/P molar ratios. HAp nanoparticles with a mean size (d50) of about 67 nm and a narrow size distribution were obtained. Furthermore, the obtained results show the advantages of the meso‐OFR over a stirred tank batch reactor due to the production, about four times faster, of smaller and more uniform HAp nanoparticles. © 2013 American Institute of Chemical Engineers AIChE J, 59: 4483–4493, 2013